Exploring Millennials' Perception of Greening Hotels in Egypt - El-Demerdash, Jailan Mohamed (جامعة الإسكندرية - كلية السياحة والفنادق, 2019)
Millennials" is a distinctive and dominant consumer group whose behavior, preferences and purchase decisions are broadly explored but not fully understood yet. Making up the largest market segment in the world, and in Egypt, they have the power to reinvent the hospitality industry and contribute to forming prospective demand for green hotels by showing willingness to adopting their environmental-friendly practices. The current study is one of the first contributions towards exploring the impact of Millennials on accepting greening hotels in Egypt. Relations among Millennials environment awareness, their acceptance of green practices and willingness to pay more were hypnotized. The study aims to enhance better understanding Millennials' perception of greening initiatives and to increase the prediction power of their intentions. Millennials' profile, their preferences and environmental decision-making process are brought under light to stimulate actions of hospitality decision-makers and hoteliers. The study questionnaire was composed of four sections and it was distributed to random Egyptian travelers' blogs and facebook groups, with approximately 8000 members. ANOVA test was used examine the study variables. The findings indicated that environmental awareness of Egyptian Millennials will not be a significant factor in their acceptance of hotel green practices, as well as, their willingness to pay more for them. However, Millennials' acceptance of hotel green practices level will have an impact on their willingness to pay more. Millennials were found to have noticeable level of environmental awareness but lack commitment to tolerating hotel green practices and their associated high prices.
Keywords: جيل الألفية -- الفنادق الخضراء -- مصر